Institutional Development, State Ownership and Corporate Cash Holdings: Evidence from China - KUSNADI, Yuanto (Institutional Knowledge at Singapore Management University, 2015)
This study examines how institutional development and state ownership influence corporate cash holdings among Chinese firms. The empirical results reveal that firms in provinces with more developed institutions (non-state-controlled firms) hold more (less) cash reserves than those in provinces with less developed institutions (state-controlled firms). Moreover, the positive effect between institutional development and cash holdings is more prominent for non-state-controlled firms. These findings are consistent with the hypothesis that more developed institutions mitigate the threat of political extraction for non-state-controlled firms, resulting in larger cash holdings among these firms. Subsequent analyses demonstrate that the impact of institutional development on cash holdings is weakened for non-state-controlled firms which have established political connections. Therefore, this study identifies one vital channel through which political connections are beneficial for non-state-controlled firms in terms of mitigating the threat of political extraction.